Metal recovery method
The lithium-draining process at elevated temperatures and controlled pH effectively addresses lithium loss in Li-AL compounds during metal recovery from lithium-ion battery waste, enhancing lithium recovery efficiency and reducing costs.
Patent Information
- Application Number
- JP2023117802
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-30
AI Technical Summary
Existing methods for recovering metals from lithium-ion battery waste, such as cobalt and nickel, result in significant lithium loss due to the formation of solid Li-AL compounds during the wet processing, which are difficult to separate effectively.
A method involving a lithium-draining process at elevated temperatures (70 °C or higher) with controlled pH conditions (3 to 3.5) is used to dissolve lithium from Li-AL-containing materials, followed by solid-liquid separation to obtain a lithium-containing solution that is reused in subsequent wet processing steps.
This approach effectively suppresses lithium loss and enhances the recovery of lithium by maintaining it within the processing cycle, reducing the need for additional concentration steps and lowering overall manufacturing costs.
Smart Images

Figure 2025014875000001_ABST
Abstract
Description
[Technical field]
[0001] This specification describes a metals recovery process. [Background technology]
[0002] In recent years, from the perspective of effective resource utilization, recovery of valuable metals such as cobalt and nickel contained in lithium-ion battery waste, which has been discarded due to product life, manufacturing defects, or other reasons, has been widely considered.
[0003] In order to recover valuable metals from lithium ion battery waste, for example, the lithium ion battery waste is roasted or subjected to other predetermined dry pretreatment to obtain battery powder, which is then subjected to wet treatment.
[0004] In the wet treatment, specifically, metals such as cobalt, nickel, manganese, lithium, aluminum, and iron in the battery powder are leached with an acid to obtain a metal-containing solution in which the metals are dissolved. Next, as described in Patent Document 1, for example, aluminum, iron, manganese, and the like are sequentially or simultaneously removed from the elements dissolved in the metal-containing solution by neutralization or solvent extraction. Thereafter, cobalt and nickel in the metal-containing solution are separated and concentrated by solvent extraction. After nickel is separated by extraction, a lithium-containing solution in which lithium is dissolved and remains is obtained. The lithium-containing solution thus obtained is concentrated by repeating solvent extraction, and then carbonated by adding carbonate or blowing in carbon dioxide gas, and the lithium contained in the lithium-containing solution is recovered as lithium carbonate.
[0005] Regarding such a metal recovery method, Patent Documents 2 and 3 describe a method for recovering metals from lithium-ion battery waste, which includes a wet treatment in which metals including lithium in lithium-ion battery waste are leached with acid and the metal is extracted from a metal-containing solution in which the metal is dissolved, and the lithium extracted by the wet treatment is used as a pH adjuster for use in the wet treatment, in order to "restrict the use of sodium hydroxide as a pH adjuster and efficiently recover metals from lithium-ion battery waste." Patent Documents 2 and 3 also describe that "a series of steps including an acid leaching step, a manganese extraction step, a cobalt extraction step, a nickel extraction step, and a hydroxide step are repeated multiple times, and at least a portion of the lithium is circulated in the liquid in the series of steps." [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 6801090 [Patent Document 2] Patent No. 7100211 [Patent Document 3] Patent No. 7100217 Summary of the Invention [Problem to be solved by the invention]
[0007] Incidentally, in the above-mentioned wet treatment, a solid Li-Al-containing material containing lithium and aluminum may be generated, for example, as an acid leaching residue obtained after leaching the metals in the battery powder with acid, or as a neutralization residue obtained when the metal-containing solution is subsequently neutralized.
[0008] When recovering metals from lithium-ion battery waste, it is desirable to separate and extract the lithium from the Li-Al-containing material described above from the aluminum in order to suppress lithium loss.
[0009] This specification proposes a metal recovery method that can effectively utilize lithium in Li-Al-containing materials by suppressing lithium loss. [Means for solving the problem]
[0010] The metal recovery method disclosed in this specification is a method for recovering metals from battery powder that is a lithium ion battery waste by performing a wet treatment, and includes a lithium leaching step of contacting a solid Li-Al-containing material containing lithium and aluminum generated in the wet treatment with a liquid, leaching the lithium in the Li-Al-containing material into the liquid at a temperature of 70°C or higher, and performing solid-liquid separation to obtain a lithium-containing solution having a pH of 3 to 10, and the lithium-containing solution obtained in the lithium leaching step is used in the wet treatment. Effect of the Invention
[0011] According to the above-mentioned metal recovery method, lithium loss can be suppressed and the lithium in the Li-Al-containing material can be effectively utilized. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a flow diagram showing the main steps of a metal recovery method according to one embodiment. [Diagram 2] FIG. 2 is a flow diagram showing a lithium leaching process for the Li-Al-containing material generated in the wet treatment of FIG. 1. [Diagram 3] FIG. 1 is a flow diagram showing an example of a pretreatment process for obtaining battery powder from lithium ion battery waste. [Figure 4] 1 is an X-ray diffraction pattern of an acid leaching residue before lithium leaching in Test Example 1 of the Examples. [Diagram 5] 1 is an X-ray diffraction pattern of the lithium leaching residue obtained in Test Example 1 of the Examples. [Figure 6] 1 is an X-ray diffraction pattern of an acid leaching residue before lithium leaching in Test Example 2 of the embodiment. [Figure 7]1 is an X-ray diffraction pattern of the lithium leaching residue obtained in Test Example 2 of the embodiment. [Figure 8] 1 is a graph showing the change in lithium leaching rate versus leaching time in the examples. [Figure 9] 1 is a graph showing the change in lithium leaching rate versus temperature during lithium leaching in the examples. [Figure 10] 1 is an X-ray diffraction pattern of the lithium leaching residue obtained in Test Example 4 of the Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the above-mentioned metal recovery method will be described in detail. In one embodiment, the metal recovery method is a method of recovering metals from battery powder of lithium-ion battery waste by performing wet treatment, and includes a lithium leaching process. The lithium leaching process targets solid Li-Al-containing material generated by wet treatment of battery powder of lithium-ion battery waste as illustrated in FIG. 1. The Li-Al-containing material contains lithium and aluminum, and in the lithium leaching process, as illustrated in FIG. 2, the lithium in the Li-Al-containing material is leached into a liquid. Thereafter, a lithium-containing solution in which lithium is dissolved is obtained by performing solid-liquid separation. Note that the Li-Al-containing material only needs to contain lithium and aluminum in at least a portion thereof, and when the Li-Al-containing material contains lithium and aluminum in a portion thereof, the remaining portion may not contain either lithium or aluminum. In addition, lithium and aluminum may be contained in the Li-Al-containing material as a Li-Al compound in which lithium and aluminum are combined, or lithium and aluminum may form separate compounds and be contained in the Li-Al-containing material. The wet treatment illustrated in FIG. 1 is repeatedly performed on different battery powder of lithium-ion battery waste. The lithium-containing solution obtained in the lithium leaching step in Fig. 2 is used in the above-mentioned wet treatment. The lithium-containing solution may be used in a wet treatment carried out on the battery powder from which the lithium-containing solution was obtained, or may be used in a wet treatment carried out on a battery powder different from the battery powder from which the lithium-containing solution was obtained.
[0014] More specifically, the lithium leaching step is performed by adjusting the pH of the lithium-containing solution after solid-liquid separation to 3 to 10, and leaching the lithium from the Li-Al-containing material. It is essential that the temperature when leaching the lithium from the Li-Al-containing material into the liquid is 70°C or higher. In this way, it is possible to effectively extract lithium from the Li-Al-containing material while suppressing the leaching of aluminum from the Li-Al-containing material. By using the lithium-containing solution obtained in this way in the wet treatment, it is possible to effectively utilize the lithium in the Li-Al-containing material and suppress the loss of lithium.
[0015] In the example shown in FIG. 1, a pretreatment process is performed on lithium-ion battery waste to obtain battery powder. This pretreatment process may include roasting, crushing, sieving, etc., as shown in FIG. 3. The battery powder is then subjected to a preliminary leaching process as necessary, and then the metal contained therein is leached in an acid leaching process. The metal-containing solution obtained by leaching the metal can be subjected to a neutralization process and a recovery process in this order. The process from the acid leaching process to the recovery of lithium is also referred to as a series of processes. In the acid leaching process, an acid leaching residue is obtained, and in the neutralization process, a neutralization residue is obtained. The acid leaching residue and / or the neutralization residue can be the Li-Al-containing material to be targeted in the lithium leaching process described above. Here, a detailed description will be given according to FIGS. 1 to 3, but FIGS. 1 to 3 are merely examples and are not limited to such specific flows.
[0016] (Lithium ion battery waste) The lithium-ion battery waste targeted here is lithium-ion secondary batteries that can be used in mobile phones and various other electronic devices, and which have been discarded due to the end of the battery product's life, manufacturing defects, or other reasons. From the perspective of effective resource utilization, valuable metals and other metals are recovered from such lithium-ion battery waste, and processing such as that shown in Figure 1 is carried out. Lithium-ion battery waste refers to lithium-ion batteries that are subject to recycling, and it does not matter whether the lithium-ion batteries are traded for a value, or traded free of charge or as industrial waste.
[0017] Lithium ion battery waste has a housing containing aluminum as an exterior that envelops the periphery. For example, this housing may be made of only aluminum, or may contain aluminum and iron, aluminum laminate, etc. In addition, lithium ion battery waste may contain a positive electrode active material made of a single metal oxide containing lithium and one selected from the group consisting of nickel, cobalt, and manganese, or a composite metal oxide containing two or more kinds, or an aluminum foil (positive electrode substrate) to which the positive electrode active material is applied and fixed with, for example, polyvinylidene fluoride (PVDF) or other organic binders. In addition, lithium ion battery waste may contain copper, iron, etc. Furthermore, the housing of lithium ion battery waste usually contains an electrolyte solution in which an electrolyte such as lithium hexafluorophosphate is dissolved in an organic solvent. For example, ethylene carbonate, diethyl carbonate, etc. may be used as the organic solvent.
[0018] (Pretreatment process) In many cases, a pretreatment process is carried out as a dry process for lithium-ion battery waste. The pretreatment process may include at least one of roasting, crushing, and sieving. The lithium-ion battery waste is turned into battery powder through the pretreatment process. The roasting, crushing, and sieving processes in the pretreatment process may be carried out individually as necessary, or may be carried out in any order. The battery powder refers to a powder obtained by separating and concentrating the components of the positive electrode active material through some pretreatment of the lithium-ion battery waste. The battery powder may be obtained by concentrating the components of the positive electrode active material through crushing and sieving the lithium-ion battery waste with or without heat treatment, resulting in a powder-like product.
[0019] In the roasting, the lithium ion battery waste is heated. When roasting is performed, for example, metals such as lithium and cobalt contained in the lithium ion battery waste can be converted into a form that is easily dissolved in the acid leaching process. In the roasting, it is preferable to heat the lithium ion battery waste at a temperature range of, for example, 450°C to 1000°C, preferably 600°C to 800°C for 0.5 hours to 4 hours. In the roasting, either heating in an air atmosphere or heating in an inert atmosphere such as nitrogen can be performed, and both heating in an air atmosphere and heating in an inert atmosphere may be performed in this order or in the reverse order. The roasting furnace may be of a batch type or a continuous type, and for example, a stationary furnace for a batch type and a rotary kiln furnace for a continuous type are available, and various other furnaces can also be used.
[0020] During roasting, at least a part of the electrolyte is removed from the lithium ion battery waste by evaporation of the electrolyte, etc. When roasting is performed, the electrolyte is removed and rendered harmless, and the organic binder is decomposed, facilitating separation of the aluminum foil and the positive electrode active material during crushing and sieving, which will be described later. Note that the composition of the positive electrode active material changes due to roasting, but here, even if it has been roasted, it will be called the positive electrode active material.
[0021] After roasting, the lithium ion battery waste can be crushed to remove the positive electrode active material and the like from the casing of the lithium ion battery waste. In the crushing, the casing of the lithium ion battery waste is destroyed, and the positive electrode active material is selectively separated from the aluminum foil on which the positive electrode active material is applied.
[0022] For the crushing, various known devices or equipment can be used, but it is particularly preferable to use an impact crusher that can crush the lithium ion battery waste by applying an impact while cutting it. Examples of this impact crusher include a sample mill, a hammer mill, a pin mill, a wing mill, a tornado mill, and a hammer crusher. A screen can be installed at the outlet of the crusher, so that the lithium ion battery waste is discharged from the crusher through the screen when it is crushed to a size that can pass through the screen.
[0023] After the lithium-ion battery waste is crushed, it is sieved using a sieve with appropriate openings, whereby aluminum and copper remain on the sieve and battery powder from which aluminum and copper have been removed to a certain extent is obtained below the sieve.
[0024] The battery powder obtained in the pretreatment step contains nickel, cobalt, lithium, manganese, etc. For example, the battery powder contains nickel in an amount of 1% to 30% by mass, cobalt in an amount of 1% to 30% by mass, lithium in an amount of 2% to 8% by mass, and manganese in an amount of 1% to 30% by mass, but is not limited thereto. The battery powder may further contain aluminum in an amount of 1% to 10% by mass, iron in an amount of 1% to 5% by mass, and copper in an amount of 1% to 10% by mass.
[0025] (Pre-leaching process) In order to extract substantially only lithium from the battery powder, the battery powder may be subjected to a preliminary leaching step prior to the acid leaching step described below. In the preliminary leaching step, the battery powder may be brought into contact with water. As a result, lithium in the battery powder is leached into the water. In this case, the battery powder as the preliminary leaching residue is subjected to the acid leaching step.
[0026] However, when the preliminary leaching step is performed, the equipment is required, and the processing time increases by performing both the preliminary leaching step and the acid leaching step. In addition, it may be necessary to control the conditions of roasting, etc., in order to effectively leach lithium with water. Therefore, the battery powder obtained as described above may be subjected to the acid leaching step without performing the preliminary leaching step.
[0027] (Acid leaching process) In the acid leaching step, the battery powder (or the battery powder as the preliminary leaching residue obtained in the preliminary leaching step in some cases) is leached with an acid leaching solution such as sulfuric acid. This results in a metal-containing solution as a post-leaching solution in which the metals in the battery powder are dissolved. If necessary, solid-liquid separation can be performed after the end of leaching to separate the acid leaching residue.
[0028] The acid leaching residue contains Li-Al compounds. The Li-Al compounds may be Li-Al composite hydroxides. If calcium and fluorine are contained in the acid leaching solution, aluminum may form compounds with calcium and fluorine during leaching of the battery powder, and may precipitate as LiCa(AlF6), Ca3Al2F8(OH)2(SO4)·2H2O, Ca2AlF7, etc. (hereinafter referred to as "LiCa(AlF6) etc."). LiCa(AlF6) etc. have a lower solubility in the acid leaching solution than Li-Al composite hydroxides, so if aluminum is precipitated in the form of LiCa(AlF6) etc., more aluminum can be contained in the acid leaching residue. Calcium and fluorine may be contained in the battery powder, but calcium and / or fluorine may be added separately. There is no particular limit to the timing of adding calcium and / or fluorine, as long as it is before the end of leaching (before solid-liquid separation after the end of leaching).
[0029] The Li-Al compound contains lithium together with aluminum. When most of the aluminum is separated and removed as an acid leaching residue, the loss of lithium removed together with the aluminum becomes apparent. Therefore, in order to recover the lithium contained in the acid leaching residue and suppress the loss of lithium, in this embodiment, the acid leaching residue containing the Li-Al compound is treated as a Li-Al-containing material, and the lithium leaching process can be performed on the Li-Al-containing material. As described above, the composition of the Li-Al compound may vary depending on whether calcium and fluorine are contained in the acid leaching solution. However, according to the lithium leaching process of this embodiment, it is possible to effectively leach the lithium contained in the Li-Al compound regardless of the composition.
[0030] The acid leaching process may involve multiple leaching stages as described below, but may also involve only a single leaching stage. After a single leaching stage, the pH of the leached solution may be less than 2.0, typically greater than or equal to 1.0 and less than 2.0.
[0031] In the acid leaching step, a diluent such as water may be added to concentrated sulfuric acid to prepare an acid leaching solution having an adjusted pH, and the battery powder may be added to the acid leaching solution. Alternatively, in the acid leaching step, a slurry may be prepared by mixing the battery powder with a diluent such as water, and concentrated sulfuric acid may be added to the slurry. In the latter case, the diluent and concentrated sulfuric acid in the slurry form the acid leaching solution, and the pH of the acid leaching solution is adjusted by the amount and pH of the diluent in the same manner as in the former case.
[0032] In the acid leaching process, multiple leaching stages may be repeated multiple times. Each leaching stage includes a first leaching stage in which the battery powder is leached with an acid leaching solution and an acid leaching residue is separated to obtain a leaching solution, and a second leaching stage in which the acid leaching residue of the first leaching stage is leached with an acid leaching solution to obtain a leaching solution. The leaching solution obtained in the final leaching stage (the second leaching stage in the case of two leaching stages, the first leaching stage and the second leaching stage) is used by being included in the acid leaching solution of the next first leaching stage. By repeating multiple leaching stages in this manner, it is possible to increase the leaching rate of the metals to be leached in the battery powder (cobalt and / or nickel, etc.) while separating most of the metals (copper, etc.) whose leaching is desired to be suppressed from being leached, and to separate them as acid leaching residue without leaching them.
[0033] As an example of repeating a plurality of leaching steps, in the first leaching step, leaching is terminated before copper is dissolved (while the copper concentration in the acid leaching solution is 0.01 g / L or less), and the acid leaching residue is extracted by solid-liquid separation. This results in a post-leaching solution that does not contain copper but contains cobalt and nickel. This post-leaching solution is sent to a subsequent step such as a neutralization step described below. Meanwhile, the acid leaching residue contains copper as well as the remaining undissolved cobalt and nickel. A second leaching step is performed to further leach cobalt and nickel from this acid leaching residue.
[0034] In the first second leaching stage, the acid leaching residue obtained in the first leaching stage is brought into contact with an acid leaching solution to leach cobalt and nickel from the acid leaching residue. In the second leaching stage, leaching is continued even after copper has been dissolved (after the copper concentration in the acid leaching solution becomes higher than 0.01 g / L). This allows almost all of the cobalt and nickel in the acid leaching residue to be leached. After copper has been dissolved and cobalt and nickel have been sufficiently leached, the leaching is terminated and the acid leaching residue is taken out by solid-liquid separation, so that the acid leaching residue contains copper but does not substantially contain cobalt or nickel. The post-leaching solution after the acid leaching residue is taken out contains cobalt, nickel and copper. In the second leaching stage, new battery powder may be added to leach not only the metals in the acid leaching residue from the first leaching stage, but also the metals in the new battery powder. In the second leaching stage, leaching is continued even after the copper has been dissolved, so that the cobalt and nickel in the new battery powder can also be sufficiently leached.
[0035] Next, in the second first leaching stage, the leaching solution obtained in the first second leaching stage is used as the acid leaching solution. At this time, new acid leaching solution may be added if necessary. In the second first leaching stage, the copper ions in the leaching solution are reduced by a substitution reaction with a metal less noble than copper in the new battery powder added thereto, and are precipitated as copper, which is included in the acid leaching residue. In addition, in the second first leaching stage, cobalt and nickel are dissolved from the new battery powder, but the process ends before copper is dissolved, so that the acid leaching residue contains copper derived from the new battery powder as well as cobalt and nickel that remain undissolved. This acid leaching residue is extracted by solid-liquid separation and is used for leaching in the second second leaching stage. The leaching solution from which the acid leaching residue is extracted contains not only cobalt and nickel dissolved from the new battery powder, but also cobalt and nickel brought in from the first leaching process, and is sent to a subsequent process.
[0036] The second second leaching stage is carried out in the same manner as the first second leaching stage, and therefore a detailed description thereof will be omitted. It is not necessary to carry out solid-liquid separation in the second leaching stage every time. If solid-liquid separation is not carried out in the second leaching stage, the post-leaching liquid containing the acid leaching residue is sent to the next leaching stage, and copper accumulates in the acid leaching residue. If solid-liquid separation is carried out in at least one of the multiple leaching stages, the acid leaching residue containing copper can be separated and removed in the second leaching stage of that leaching stage. Preferably, solid-liquid separation is carried out in each second leaching stage, and the acid leaching residue containing copper is removed each time.
[0037] Aluminum that may be contained in the post-leaching solution can be removed in a subsequent neutralization step, as described below. When multiple leaching stages are performed, the pH of the post-leaching solution obtained after the first leaching stage is completed and solid-liquid separation may be somewhat high, such as 2.5 to 3.5. When the pH is somewhat high, a large amount of aluminum is removed together with calcium. Also, the oxidation-reduction potential (ORP value, silver / silver chloride potential standard) may be 100 mV or less.
[0038] When calcium and / or fluorine are added to the acid leachate in multiple leaching stages, the timing of addition is not particularly important, but it is preferable to add them in the first leach stage, in which case the pH tends to be relatively high as described above, and most of the aluminum can be precipitated.
[0039] The post-leaching solution may have, for example, an aluminum concentration of 1.0 g / L to 20 g / L, a nickel concentration of 10 g / L to 50 g / L, a cobalt concentration of 10 g / L to 50 g / L, a manganese concentration of 0 g / L to 50 g / L, an iron concentration of 0.1 g / L to 5.0 g / L, a copper concentration of 0.005 g / L to 0.2 g / L, and a fluoride concentration of 0.01 g / L to 20 g / L.
[0040] (neutralization process) In the case where the post-leaching solution obtained in the acid leaching step contains aluminum, a neutralization step can be carried out after the acid leaching step. Here, the solution obtained after the acid leaching step and containing the metal ions due to the dissolution of the metal in the acid leaching step is referred to as a metal-containing solution.
[0041] In the neutralization step, the pH of the metal-containing solution is increased, and the neutralization residue is separated to obtain a neutralized liquid. The neutralization step may include a dealumination step. In the dealumination step, the pH of the metal-containing solution is increased to precipitate and remove at least a portion of the aluminum. When the metal-containing solution contains iron, the neutralization step preferably also includes a de-ironization step to remove the iron after the dealumination step. In the de-ironization step, an oxidizing agent is added to the dealumination solution obtained in the dealumination step, and an alkali is further added to increase the pH, thereby removing the iron. This results in a neutralized liquid such as a de-ironization liquid.
[0042] When removing aluminum in the dealumination stage, an alkaline pH adjuster may be added to the metal-containing solution to raise the pH to, for example, within a range of 2.5 to 5.0 (preferably, 3.0 to 4.5). In addition, in the dealumination stage, the oxidation-reduction potential (ORP value, based on silver / silver chloride potential) may be 50 mV to 400 mV (250 mV to 350 mV at the end). At this time, the temperature of the metal-containing solution may be 50°C to 90°C. After the aluminum is precipitated, solid-liquid separation such as filtration is performed using known devices and methods such as a filter press or a thickener, and neutralization residue is removed to obtain a dealumination liquid.
[0043] The neutralization residue contains Li-Al compounds. The Li-Al compounds may be Li-Al complex hydroxides. If calcium and fluorine are contained in the metal-containing solution, aluminum may form compounds with calcium and fluorine in the dealumination stage, and may precipitate as LiCa(AlF6), Ca3Al2F8(OH)2(SO4)·2H2O, Ca2AlF7, etc. (hereinafter referred to as "LiCa(AlF6) etc."). LiCa(AlF6) etc. have a lower solubility in the metal-containing solution than Li-Al complex hydroxides, so if aluminum is precipitated in the form of LiCa(AlF6) etc., more aluminum can be contained in the neutralization residue. Calcium and fluorine may be contained in the metal-containing solution, but calcium and / or fluorine may be added separately. There is no particular limit to the timing of adding calcium and / or fluorine as long as it is before the dealumination stage is completed.
[0044] When the neutralization residue contains Li-Al compounds, the neutralization residue can be treated as a Li-Al-containing material and the Li-Al-containing material can be subjected to a lithium leaching process in order to recover lithium from the neutralization residue. As described above, the composition of the Li-Al compound can vary depending on whether calcium and fluorine are contained in the metal-containing solution. However, according to the lithium leaching process of the present embodiment, it is possible to effectively leach the lithium contained in the Li-Al compound, regardless of the composition of the Li-Al compound.
[0045] Next, in the iron removal stage, an oxidizing agent can be added to the dealumination liquid to remove iron from the dealumination liquid. The addition of the oxidizing agent oxidizes the iron in the liquid from divalent to trivalent, and the trivalent iron precipitates as an oxide or hydroxide at a lower pH than the divalent iron. In many cases, the iron precipitates as a solid such as iron hydroxide (Fe(OH)3). The precipitated iron can be removed as a neutralization residue by solid-liquid separation.
[0046] The oxidizing agent is not particularly limited as long as it can oxidize iron, but it is preferably manganese dioxide, a positive electrode active material, and / or a manganese-containing leaching residue obtained by leaching the positive electrode active material. The manganese-containing leaching residue obtained by leaching the positive electrode active material with an acid or the like may contain manganese dioxide. When the above-mentioned positive electrode active material or the like is used as the oxidizing agent, a precipitation reaction occurs in which manganese dissolved in the liquid becomes manganese dioxide, so that the precipitated manganese can be removed together with iron. In order to precipitate iron, the ORP value during oxidation is preferably 300 mV to 900 mV. After the addition of the oxidizing agent, an alkaline pH adjuster is added to adjust the pH to, for example, a range of 3.0 to 4.5, thereby precipitating iron.
[0047] Specific examples of alkaline pH adjusters used in the dealumination and iron removal stages include lithium hydroxide, sodium hydroxide, sodium carbonate, ammonia, etc. As lithium hydroxide, a lithium hydroxide solution obtained in the recovery process described below can be used as shown in Figure 1. In this case, lithium is circulated within a series of steps in the wet treatment.
[0048] (Recovery process) In the recovery step, manganese is extracted and removed from the metal-containing solution obtained in the neutralization step as necessary, and nickel and cobalt are then recovered.
[0049] In the extraction of manganese, an extractant containing a phosphate ester extractant is used, and manganese, and in some cases aluminum that was not removed in the neutralization step, are extracted and removed by solvent extraction. Here, an example of the phosphate ester extractant is di-2-ethylhexyl phosphoric acid (abbreviation: D2EHPA or product name: DP-8R). The extractant may be a mixture of a phosphate ester extractant and an oxime extractant.
[0050] During extraction, the equilibrium pH is preferably 2.3 to 3.5. For the alkaline pH adjuster used at this time, it is preferable to use a lithium hydroxide solution obtained as described below, but separately prepared sodium hydroxide or the like may also be used. During extraction, it is desirable to perform extraction by countercurrent multi-stage extraction in which the aqueous phase and the solvent used in each extraction flow in opposite directions. In this way, it is possible to suppress the extraction of cobalt, nickel, and lithium, and to increase the extraction rate of manganese. In the case of countercurrent multi-stage extraction, it is also effective to set the equilibrium pH during the first extraction stage within the above-mentioned range, and to lower the equilibrium pH during each extraction stage. This allows the manganese extraction liquid to be obtained.
[0051] In the recovery of cobalt, cobalt is separated from the manganese extraction liquid obtained after manganese extraction by solvent extraction. Here, it is preferable to use a solvent containing a phosphonate ester extractant. Among them, 2-ethylhexyl phosphonate (trade name: PC-88A, Ionquest801) is particularly suitable from the viewpoint of separation efficiency between nickel and cobalt. The extractant may be diluted with a hydrocarbon organic solvent such as an aromatic, paraffinic, or naphthenic solvent to a concentration of 10% by volume to 30% by volume, and this may be used as the solvent.
[0052] When cobalt is extracted, the equilibrium pH during extraction can be preferably 5.0 to 6.0. In this case, as the pH adjuster, it is preferable to use a lithium hydroxide solution obtained as described below, but separately prepared sodium hydroxide or the like can also be used. This allows the cobalt in the manganese extraction solution to be extracted into the solvent. In addition, when extracting cobalt, it is desirable to perform the extraction by a countercurrent multi-stage extraction in which the aqueous phase and the solvent used in each extraction flow in opposite directions. In this way, the extraction rate of cobalt can be increased while suppressing the extraction of nickel and lithium.
[0053] During the extraction of cobalt, not only cobalt but also nickel, lithium, etc., which become impurities in the cobalt extraction process, may be extracted in small amounts into the solvent. In this case, if necessary, the solvent from which cobalt was extracted may be scrubbed one or more times using a scrubbing solution such as a sulfuric acid acid solution having a pH of 3.5 to 5.5 to remove impurities such as nickel that may be contained in the solvent. The post-scrubbing solution may contain nickel and lithium. Therefore, it is desirable to use a part or all of the post-scrubbing solution for the extraction of cobalt (that is, to mix a part or all of the post-scrubbing solution with a manganese extraction solution and use the resulting solution as a pre-extraction solution to extract cobalt). This allows nickel and lithium to be circulated or retained in the process without loss. However, if the solvent from which cobalt was extracted does not contain nickel or lithium, scrubbing may not be performed.
[0054] Thereafter, stripping is performed on the solvent from which the cobalt has been extracted. The stripping solution used for stripping may be any inorganic acid such as sulfuric acid, hydrochloric acid, or nitric acid, but sulfuric acid is preferable when obtaining sulfate by crystallization, which will be described later. Here, the stripping is performed under pH conditions such that as much of the cobalt as possible is extracted from the organic phase (solvent) into the aqueous phase (stripping solution). Specifically, the pH is preferably in the range of 2.0 to 4.0. The O / A ratio and the number of times can be appropriately determined. The liquid temperature may be room temperature, but is preferably 10°C to 50°C.
[0055] The stripped liquid, such as the cobalt sulfate solution obtained by stripping cobalt, is crystallized. In this crystallization, the stripped liquid is heated to, for example, 40°C to 120°C and concentrated to crystallize cobalt, thereby obtaining a cobalt salt, such as cobalt sulfate. The cobalt salt thus obtained preferably has a nickel content of 5 mass ppm or less, and nickel has been sufficiently removed, so that it can be effectively used as a raw material for the manufacture of lithium-ion secondary batteries and other batteries. Here, the crystallized liquid may contain cobalt and lithium that have not crystallized. Therefore, the crystallized liquid may be returned to the stripped liquid to be subjected to crystallization and mixed, and used for recrystallization, or may be used for the purpose of adjusting the cobalt concentration of the scrubbing liquid used in scrubbing after cobalt extraction, or may be used for cobalt extraction. By repeatedly using the liquid in this manner within the process, cobalt and lithium can be circulated or retained within the process and concentrated without loss.
[0056] In the recovery of nickel, a carboxylic acid extractant is preferably used for the cobalt extraction liquid obtained after cobalt extraction to separate nickel. Examples of carboxylic acid extractants include neodecanoic acid and naphthenic acid, and among them, neodecanoic acid is preferred because of its nickel extraction ability. The extractant may be diluted with a hydrocarbon organic solvent such as an aromatic, paraffinic, or naphthenic solvent to a concentration of 10% by volume to 30% by volume, and this may be used as the solvent.
[0057] In extracting nickel, the equilibrium pH is preferably 6.0 to 8.0. The pH adjuster used to adjust the pH at this time may be sodium hydroxide or the like, but it is preferable to use a lithium hydroxide solution obtained as described below. In the extraction of nickel, it is desirable to perform extraction by countercurrent multi-stage extraction, as in the extraction of cobalt described above. In this way, the extraction of lithium can be suppressed and the extraction rate of nickel can be increased.
[0058] The solvent from which nickel has been extracted may be scrubbed one or more times as necessary using a scrubbing solution such as a sulfuric acid solution having a pH of 5.0 to 6.0 to remove impurities such as lithium and sodium that may be contained in the solvent. The post-scrubbing solution may contain lithium. Therefore, it is desirable to use a part or all of the post-scrubbing solution for nickel extraction (that is, to mix a part or all of the post-scrubbing solution with a post-cobalt extraction solution and use the resulting solution as a pre-extraction solution to extract nickel). This allows lithium to be circulated or retained in the process and concentrated without loss. However, if the solvent from which nickel has been extracted does not contain lithium, scrubbing may not be performed.
[0059] Next, the solvent is back-extracted using a back-extraction solution such as sulfuric acid, hydrochloric acid, or nitric acid. When crystallization is to be performed after that, sulfuric acid is preferable. The pH is preferably in the range of 1.0 to 3.0, more preferably 1.5 to 2.5. The O / A ratio and the number of times can be appropriately determined, but the O / A ratio may be, for example, 5 to 1.
[0060] When a stripping solution such as a nickel sulfate solution is obtained by stripping, it can be electrolyzed and dissolved as necessary, then heated to 40°C to 120°C to crystallize nickel as a nickel salt such as nickel sulfate. This results in a nickel salt. Here, the crystallization solution may contain nickel and lithium that have not crystallized. Therefore, the crystallization solution is preferably used for recrystallization by returning it to the stripping solution to be subjected to crystallization and mixing it, or for the purpose of adjusting the nickel concentration of the scrubbing solution used for scrubbing after nickel extraction, or for nickel extraction. By repeatedly using it in this manner in the process, nickel and lithium can be circulated or retained in the process and concentrated without loss.
[0061] The nickel-extracted solution (lithium sulfate solution, etc.) after nickel extraction can be used as at least a part of the dilution solution for adjusting the pH of the acid leaching solution by diluting concentrated sulfuric acid in the acid leaching step, as shown in Fig. 1. This allows the lithium contained in the nickel-extracted solution to be circulated in a series of steps including the acid leaching step, neutralization step, and recovery step. Preferably, after the lithium concentration in the nickel-extracted solution has increased to a certain degree by circulating lithium in this way, the hydroxide described below can be carried out.
[0062] The nickel extraction solution obtained after nickel extraction is a solution such as a lithium sulfate solution containing substantially only lithium as a result of separation of each metal. If necessary, trace amounts of cations such as nickel and magnesium can be removed using an ion exchange resin or a chelating resin, and then hydroxide can be performed to obtain a lithium hydroxide solution. Examples of hydroxide can include the carbonation and chemical conversion method using calcium hydroxide after producing lithium carbonate, the chemical conversion method using barium hydroxide, and a method using electrodialysis, as described below.
[0063] In the case of the carbonation and chemical conversion method, first, a lithium carbonate solution is obtained by adding carbonate or blowing carbon dioxide into the nickel-extracted solution. Then, in the so-called chemical conversion method, calcium hydroxide is added to the lithium carbonate solution to generate a lithium hydroxide solution under the reaction formula Li2CO3+Ca(OH)2→2LiOH+CaCO3. Calcium that may remain in the solution can be removed by using a cation exchange resin or a chelating resin.
[0064] When barium hydroxide is used, it is added to the solution after nickel extraction, and a lithium hydroxide solution can be obtained based on the reaction Li2SO4+Ba(OH)2→2LiOH+BaSO4. Note that barium that may dissolve in the solution at this time can be separated and removed using a cation exchange resin or a chelating resin.
[0065] In electrodialysis, in a bipolar membrane electrodialysis device, the nickel extraction solution is placed in the desalting compartment between the anion exchange membrane and the cation exchange membrane, and pure water is placed in the acid compartment between the bipolar membrane and the anion exchange membrane and the alkaline compartment between the cation exchange membrane and the bipolar membrane, and a voltage is applied between the electrodes. Then, lithium in the metal-containing solution in the desalting compartment moves to the alkaline compartment, where the bipolar membrane decomposes the pure water into hydroxide ions to obtain a lithium hydroxide solution. The anions of inorganic acids such as sulfuric acid in the metal-containing solution in the desalting compartment pass through the anion exchange membrane and move to the acid compartment.
[0066] At least a part of the lithium hydroxide solution obtained as described above can be effectively used as an alkaline pH adjuster for use in at least one step selected from the group consisting of the neutralization step and the recovery step (when a plurality of extractions are performed in the recovery step, at least one of the extractions).
[0067] As described above, if the lithium hydroxide solution is returned as a pH adjuster to the neutralization step or to the extraction of manganese, etc., the lithium concentration in the solution may gradually increase due to the lithium in the battery powder newly added. Depending on the lithium concentration, the lithium hydroxide solution obtained by the hydroxide oxidation may be subjected to a crystallization procedure such as heating and concentration or reduced pressure distillation to precipitate and recover lithium hydroxide.
[0068] (Lithium leaching process) For example, a solid Li-Al-containing material containing lithium and aluminum may be generated as an acid leaching residue in the acid leaching step described above (an acid leaching residue obtained in the final leaching step if a plurality of leaching steps are performed as described above in the acid leaching step, or an acid leaching residue obtained in the second leaching step if the acid leaching step includes two steps, a first leaching step and a second leaching step), a neutralization residue in the neutralization step, etc. In order to recover lithium from the Li-Al-containing material, the Li-Al-containing material is subjected to a lithium leaching step.
[0069] However, the Li-Al-containing material is not limited to the above-mentioned acid leaching residue or neutralization residue, as long as it is generated during the treatment of lithium-ion battery waste and contains lithium and aluminum. The Li-Al-containing material typically contains LiCa(AlF6) or Li-Al composite hydroxide as a Li-Al compound, but may also contain, in addition to lithium and aluminum, a compound that does not contain lithium and aluminum, such as calcium sulfate, which will be described later.
[0070] In the lithium leaching step, the Li-Al-containing material is brought into contact with a liquid such as water, and lithium in the Li-Al-containing material is leached into the liquid at a temperature of 70°C or higher, preferably 80°C or higher. If the leaching temperature is too low, not much lithium can be leached. On the other hand, if the leaching temperature is too high, there is a risk of increased energy consumption. For this reason, the leaching temperature is preferably 80°C to 90°C.
[0071] As long as the pH of the lithium-containing solution obtained by solid-liquid separation after lithium leaching can be adjusted to within a predetermined range, the pH of the liquid before leaching (before contacting with the Li-Al-containing material) or during leaching is not particularly important. Typically, the liquid is water, more specifically, tap water, industrial water, distilled water, purified water, ion-exchanged water, pure water, ultrapure water, etc. However, as described later, when a liquid containing calcium is used, the leaching rate of lithium is improved, so the water as the liquid may contain such other substances, and the pH before or during leaching may change depending on the substance.
[0072] When leaching lithium, it is preferable that the liquid contains calcium in the form of calcium sulfate or the like. Specifically, if the Li-Al-containing material already contains calcium, the liquid will contain calcium by contacting the Li-Al-containing material. Also, after adding calcium to the Li-Al-containing material, the lithium leaching step may be performed. Also, calcium may be added to the liquid while the lithium in the Li-Al-containing material is being leached in the lithium leaching step. When calcium is contained in the liquid in this way, the leaching rate of lithium in the Li-Al-containing material is increased and the leaching of aluminum can be more effectively suppressed. This is considered to be because the aluminum is recombined with calcium and precipitated after the Li-Al-containing material is dissolved by the calcium contained in the liquid, thereby suppressing the leaching of aluminum. When the Li-Al-containing material contains calcium, it may not be necessary to add calcium to the liquid, but calcium may be added to the liquid separately regardless of whether the Li-Al-containing material contains calcium or not. As mentioned above, when calcium is added to the acid leaching solution in the acid leaching process, or when calcium is added to the metal-containing solution in the neutralization process, calcium may be contained in the Li-Al-containing material as the acid leaching residue or neutralization residue.
[0073] When calcium such as calcium sulfate is added to the liquid, it is preferable to determine the amount of calcium added depending on the aluminum content of the Li-Al-containing material. Taking into consideration the calcium content that may be contained in the Li-Al-containing material, the amount of calcium added may be adjusted so that the total number of moles of calcium is 0.5 to 3.0 times the number of moles of aluminum in the Li-Al-containing material.
[0074] The liquid may also contain sulfuric acid. When a liquid containing sulfuric acid is used to leach lithium, lithium can be further leached. The amount of sulfuric acid added is preferably 0.5 to 1.0 times the mole number of lithium. In this case, the pH of the liquid may be 3 to 4.
[0075] If the lithium concentration in the liquid becomes too high during the leaching of lithium, lithium may not be leached any further. Therefore, from the viewpoint of improving the leaching rate of lithium, it is preferable to adjust the lithium concentration of the lithium-containing solution obtained by solid-liquid separation after the leaching of lithium into the liquid to 150 mg / L or less. For example, the lithium concentration of the lithium-containing solution after leaching can be adjusted by changing the pulp concentration according to the lithium content in the Li-Al-containing material. The pulp concentration here means the mass of the Li-Al-containing material relative to the amount of the liquid used for leaching lithium.
[0076] The lithium leaching time is preferably 20 minutes or more. This is because the lithium leaching rate tends to increase with the leaching time. However, if the leaching time is too long, the efficiency decreases. Therefore, the lithium leaching time is preferably 60 to 500 minutes.
[0077] The pH of the lithium-containing solution obtained by solid-liquid separation after leaching lithium in the lithium leaching step is in the range of 3 to 10, preferably 4 to 9. If the pH is too low, there is a concern that aluminum dissolution will increase, and if the pH is too high, there is a risk that unnecessary alkali will need to be added. The pH of the liquid before and during leaching or additives can be adjusted so that the pH of the lithium-containing solution falls within the above range. The above pH refers to the pH when the lithium-containing solution is lowered to room temperature after lithium leaching and solid-liquid separation.
[0078] The lithium-containing solution is used in the above-mentioned wet treatment. Specifically, the lithium-containing solution can be used as at least a part of the water to be contacted with the battery powder in the preliminary leaching step, or as at least a part of the acid leaching solution in the acid leaching step (as at least a part of the diluent for adjusting the pH of the acid leaching solution). In particular, when the lithium-containing solution is used in the acid leaching step, the lithium-containing solution replaces the diluent, such as water that does not contain lithium, and this can increase the lithium concentration of the solution after leaching, thereby contributing to maintaining a high lithium concentration in the solution in a series of steps.
[0079] Lithium that is not recovered as lithium hydroxide in the hydroxide of lithium ions after the nickel extraction process described above will be lost if it is discarded as it is. The amount of lithium recovered is the difference between the amount of lithium ions in the nickel extraction solution and the amount of lithium lost, so the higher the lithium recovery rate is, the higher the lithium ion concentration in the nickel extraction solution is. Here, in the past, since the lithium ion concentration in the nickel extraction solution was low, it was necessary to increase the lithium ion concentration in the solution by performing a lithium concentration process, but in this embodiment, it is not necessary to perform such a lithium concentration process, and a high-concentration lithium aqueous solution can be obtained without performing a complicated process, so that the loss of lithium in the process and the production cost can be reduced.
[0080] The lithium-containing solution can also be used as at least a part of the cleaning solution used to clean the acid leaching residue generated in the acid leaching step or the neutralization residue generated in the neutralization step. In this case, the post-cleaning solution obtained after the cleaning can be returned to the series of steps. When the lithium-containing solution is used as the cleaning solution for the acid leaching residue, if the leaching in the acid leaching step is only one stage, the post-cleaning solution for the acid leaching residue can be mixed with the post-leaching solution and returned to the series of steps. Alternatively, if the leaching in the acid leaching step is multiple stages, the post-cleaning solution for the acid leaching residue generated in the first leaching step can be sent to a subsequent step such as a neutralization step together with the post-leaching solution obtained in the first leaching step, and the post-leaching solution obtained in the second leaching step can be used in the next first leaching step, while the post-cleaning solution for the acid leaching residue generated in the second leaching step can be used in the next first leaching step together with the post-leaching solution. In this way, the loss of lithium contained in the Li-Al-containing material can be suppressed, and the lithium can be effectively utilized. Furthermore, compared to using water that does not contain lithium as a cleaning solution, if a lithium-containing solution is used as the cleaning solution, the lithium ion concentration in the series of steps after the post-cleaning solution is returned to the series of steps can be maintained at a higher concentration.
[0081] On the other hand, the lithium leaching residue that remains after the lithium leaching process contains a certain amount of aluminum. When the lithium leaching process is performed on a Li-Al-containing material containing an acid leaching residue and / or a neutralization residue, the lithium leaching residue may contain Ca3Al2F8(OH)2SO4 in addition to LiCa(AlF6) that remains after the lithium leaching process. The presence or absence of such components can be confirmed by X-ray diffraction (XRD). EXAMPLES
[0082] Next, the lithium leaching step of the metal recovery method described above was experimentally carried out to verify its effectiveness, which will be described below, although the description here is merely for illustrative purposes and is not intended to be limiting.
[0083] Lithium ion battery waste was subjected to pretreatment including roasting to obtain battery powder. In the roasting, the lithium ion battery waste was first heated in an inert atmosphere, and then the atmosphere was switched to air and heated. The following tests were performed using such battery powder.
[0084] (Test Example 1) The metals in the battery powder were leached by acid leaching, which included a first leaching stage and a second leaching stage as described above. Thus, an acid leaching residue was obtained in the second leaching stage. The lithium, aluminum and calcium contents of the acid leaching residue are shown in Table 1.
[0085] [Table 1]
[0086] The above-mentioned acid leaching residue of 2 g or 20 g was contacted with water as a liquid, and lithium leaching was performed under different pulp concentrations (10 g / L or 100 g / L) and different temperature conditions (90 ° C or 25 ° C). Here, the leaching time was 300 minutes. The mass and distribution ratio (mass ratio when the components in the acid leaching residue are 100) of lithium, aluminum, and calcium contained in the lithium leaching residue (solid) and the lithium-containing solution (liquid) obtained after solid-liquid separation are shown in Tables 2 to 4. The pH of the lithium-containing solution at room temperature was about 5 in the tests in Tables 2 and 3, and about 6 in the test in Table 4. In addition, in the test in Table 2 where the temperature was 90 ° C and the pulp concentration was 10 g / L, the mass ratio of the components in the acid leaching residue and the lithium leaching residue when the components in the battery powder are 100 is shown in Table 5.
[0087] [Table 2]
[0088] [Table 3]
[0089] [Table 4]
[0090] [Table 5]
[0091] From Tables 2 to 4, it can be seen that when the temperature during lithium leaching is increased to 90°C, more lithium is leached and contained in the lithium-containing solution than when the temperature is 25°C. Also, from Table 5, it can be seen that the mass ratio of lithium in the lithium leaching residue is significantly lower than the mass ratio of lithium in the acid leaching residue. In other words, from Table 5, it can be seen that most of the lithium in the acid leaching residue is distributed to the lithium-containing solution obtained by performing solid-liquid separation after the lithium leaching step. This shows that, compared to the case where the acid leaching residue is discarded as it is, the loss of lithium can be effectively suppressed by performing high-temperature lithium leaching on the acid leaching residue and recovering lithium from the lithium-containing solution by the above-mentioned method. In addition, in all tests, the leaching of aluminum was suppressed.
[0092] In addition, the acid leaching residue before lithium leaching and the lithium leaching residue obtained after lithium leaching at 90°C were analyzed by powder X-ray diffraction method using a Rigaku Smartlab X-RAY DIFFRACTOMETER with Cu Kα as the X-ray source under the conditions of 2θ=5-90°, step of 0.01°, and scan speed of 20° / min, and the X-ray diffraction patterns shown in Figures 4 and 5 were obtained. As shown in Figure 4, Ca3Al2F8(OH)2SO4 was not confirmed in the acid leaching residue, whereas, as shown in Figure 5, Ca3Al2F8(OH)2SO4 was contained in the lithium leaching residue. From this, it is presumed that during lithium leaching, the Li-Al compound in the acid leaching residue decomposed and aluminum dissolved, and then the aluminum recombined with calcium and precipitated. It is considered that the leaching of aluminum was effectively suppressed here.
[0093] (Test Example 2) The metals in the battery powder were leached by acid leaching, which included a first leaching stage and a second leaching stage as described above. Thus, an acid leaching residue was obtained in the second leaching stage. The lithium, aluminum and calcium contents of the acid leaching residue are shown in Table 6.
[0094] [Table 6]
[0095] The above-mentioned acid leaching residue (4 g) was brought into contact with water as a liquid, and lithium leaching was performed under different temperature conditions (90°C or 70°C). Here, the pulp concentration was 20 g / L, and the leaching time was 300 minutes. The mass and distribution ratio (mass ratio when the components in the acid leaching residue are taken as 100) of lithium, aluminum, and calcium contained in the lithium leaching residue (solid) and the lithium-containing solution (liquid) obtained after solid-liquid separation are shown in Tables 7 and 9, respectively, and the mass ratios of the components in the acid leaching residue and the lithium leaching residue when the components in the battery powder are taken as 100 are shown in Tables 8 and 10, respectively. The pH of the lithium-containing solution was around 5 at room temperature.
[0096] [Table 7]
[0097] [Table 8]
[0098] [Table 9]
[0099] [Table 10]
[0100] From Tables 7 and 9, it can be seen that when the temperature during lithium leaching is increased to 90°C, more lithium is leached and contained in the lithium-containing solution than when the temperature is 70°C. Also, from Tables 8 and 10, it can be seen that lithium loss can be effectively suppressed by performing lithium leaching at high temperatures. In addition, in all tests, the leaching of aluminum was suppressed.
[0101] In addition, the X-ray diffraction pattern of the acid leaching residue before lithium leaching is shown in Figure 6, and the X-ray diffraction pattern of the lithium leaching residue obtained after lithium leaching at 90°C is shown in Figure 7. As shown in Figure 6, the acid leaching residue does not contain Ca3Al2F8(OH)2SO4, but as shown in Figure 7, the lithium leaching residue contains Ca3Al2F8(OH)2SO4. From this, it is considered that during lithium leaching, the Li-Al compound in the acid leaching residue decomposes and aluminum dissolves, and then the aluminum recombines with calcium and precipitates, and as a result, the leaching of aluminum is effectively suppressed.
[0102] (Test Example 3) Lithium leaching was carried out in the same manner as in Test Example 2, except that the temperature was 70°C and the leaching time was 5 or 8 hours, using the acid leaching residue having the composition shown in Table 6. The mass and distribution ratios (mass ratios when the components in the acid leaching residue are taken as 100) of lithium, aluminum and calcium contained in the lithium leaching residue (solid) and the lithium-containing solution (liquid) obtained after solid-liquid separation are shown in Tables 11 and 13, respectively, and the mass ratios of the components in the acid leaching residue and the lithium leaching residue when the components in the battery powder are taken as 100 are shown in Tables 12 and 14, respectively. The pH of the lithium-containing solution was around 6 at room temperature.
[0103] [Table 11]
[0104] [Table 12]
[0105] [Table 13]
[0106] [Table 14]
[0107] (Test Example 4) Lithium leaching was performed using the acid leaching residue having the composition shown in Table 6 in the same manner as in Test Example 2, except that the temperature was 90°C or 80°C and the leaching time was 8 hours, 5 hours, 2 hours or 20 minutes. Here, the pulp concentration was 20g / L. The mass and distribution ratio (mass ratio when the components in the acid leaching residue are taken as 100) of lithium, aluminum and calcium contained in the lithium leaching residue (solid) and the lithium-containing solution (liquid) obtained after solid-liquid separation are shown in Tables 15, 17, 19 and 21, respectively, and the mass ratio of the components in the acid leaching residue and the lithium leaching residue when the components in the battery powder are taken as 100 are shown in Tables 16, 18, 20 and 22, respectively. The pH of the lithium-containing solution at room temperature was about 5 in the tests in Tables 15, 17 and 21, and about 6 in the test in Table 19.
[0108] [Table 15]
[0109] [Table 16]
[0110] [Table 17]
[0111] [Table 18]
[0112] [Table 19]
[0113] [Table 20]
[0114] [Table 21]
[0115] [Table 22]
[0116] From the above tests, the change in lithium leaching rate versus leaching time is shown in the graph in Figure 8. Figure 8 plots the test results shown in Tables 7, 15, 17, and 19, and all of these tests had a pulp concentration of 20 g / L and a temperature of 90°C, and only the leaching time was changed. Figure 9 also shows a graph of the change in lithium leaching rate versus temperature during lithium leaching, obtained from the test results in Tables 4, 7, 9, and 21.
[0117] As shown in Figure 8, the longer the leaching time, the higher the lithium leaching rate. Also, from Figure 9, it can be seen that if the temperature during lithium leaching is 70°C or higher, the lithium leaching rate is sufficiently high, and if it is 80°C or higher, a large amount of lithium is leached out.
[0118] The acid leaching residue before lithium leaching is the same as the acid leaching residue used in Test Example 2, and its X-ray diffraction pattern is shown in FIG. 6. The X-ray diffraction patterns of the lithium leaching residues (residues in Tables 17 and 18) obtained after leaching lithium at 90° C. for 2 hours are shown in FIG. 10. Comparing the X-ray diffraction patterns in FIG. 6 and 10 with the X-ray diffraction pattern in FIG. 7 for the lithium leaching residues (residues in Tables 7 and 8) obtained after leaching lithium at 90° C. for 5 hours, the strongest peak on the left side of FIG. 6 is either CaSO4 or Li-Al composite hydroxide, but the intensity is not so much reduced in the 2-hour leaching in FIG. 10, whereas the intensity is reduced in the 5-hour leaching in FIG. 7. From this, it is recognized that the strongest peak on the left side is not the peak of CaSO4, which dissolves in a relatively short time, but the peak of Li-Al composite hydroxide. As shown in Figure 7, the intensity of this peak is reduced after 5 hours of leaching, so it is presumed that the Li-Al composite hydroxide was dissolved here. From this result, it can be said that even if the Li-Al composite hydroxide is dissolved, a large amount of lithium can be leached, as shown in Tables 7 and 8.
[0119] (Test Example 5) Lithium leaching was performed using the acid leaching residue having the composition shown in Table 6 in the same manner as in Test Example 2, except that the acid leaching residue was contacted with a liquid obtained by adding sulfuric acid in different amounts to water. The amount of sulfuric acid added was 0.5 times the molar amount and 1 time the molar amount of lithium in the acid leaching residue. Here, the pulp concentration was 20 g / L, the leaching time was 5 hours, and the temperature during leaching was 90°C. The mass and distribution ratio (mass ratio when the components in the acid leaching residue are 100) of lithium, aluminum, and calcium contained in the lithium leaching residue (solid) and the lithium-containing solution (liquid) obtained after solid-liquid separation are shown in Tables 23 and 25, respectively, and the mass ratios of the components in the acid leaching residue and the lithium leaching residue when the components in the battery powder are 100 are shown in Tables 24 and 26, respectively. The pH of the lithium-containing solution at room temperature was 4.68 in the test in Table 23 and 3.44 in the test in Table 25.
[0120] [Table 23]
[0121] [Table 24]
[0122] [Table 25]
[0123] [Table 26]
[0124] From Tables 23 and 25, it was found that lithium can be leached while suppressing the leaching of aluminum even when sulfuric acid is added. By limiting the amount of sulfuric acid added to a certain amount and not lowering the pH too much, it is possible to effectively suppress the leaching of aluminum, as shown in Table 23. From the results of these tests, it is considered that the pH of the lithium-containing solution is preferably 4.5 or higher.
[0125] (Test Example 6) The metals in the battery powder were leached by acid leaching including the first and second leaching stages as described above, and the metal-containing solution obtained was neutralized to precipitate mainly aluminum, to obtain a neutralized residue A having the composition shown in Table 27.
[0126] [Table 27]
[0127] 1.5 g of the neutralized residue A was contacted with water as a liquid, and lithium leaching was performed at 90°C. Here, the pulp concentration was 7.5 g / L, and the leaching time was 300 minutes. The mass and distribution ratio (mass ratio when the components in the neutralized residue A are 100) of lithium, aluminum, and calcium contained in the lithium leaching residue (solid) and the lithium-containing solution (liquid) obtained after solid-liquid separation, as well as the mass ratio of the components in the neutralized residue A and the lithium leaching residue when the components in the battery powder are 100 are shown in Tables 28 and 29, respectively. The pH of the lithium-containing solution was about 6 at room temperature.
[0128] [Table 28]
[0129] [Table 29]
[0130] From Table 28, it can be seen that when neutralization residue is used, lithium is leached out in a relatively large amount, although the leaching rate is lower than when acid leaching residue is used, and aluminum is also leached out to a certain extent.
[0131] In addition, the above neutralized residue A was used to carry out the same lithium leaching except that calcium sulfate was added to the water. The amount of calcium sulfate added was 1 time the original number of moles of aluminum. Including the calcium contained in the neutralized residue A, the number of moles of calcium was 1.4 times the number of moles of aluminum. The mass and distribution ratio (mass ratio when the components in the neutralized residue A are 100) of lithium, aluminum, and calcium contained in the lithium leaching residue (solid) and the lithium-containing solution (liquid) obtained after solid-liquid separation, and the mass ratio of the components in the neutralized residue A and the lithium leaching residue when the components in the battery powder are 100 are shown in Tables 30 and 31, respectively. The pH of the lithium-containing solution was around 5 at room temperature.
[0132] [Table 30]
[0133] [Table 31]
[0134] From Table 30, it can be seen that the addition of calcium suppresses the leaching of aluminum and increases the leaching of lithium.
[0135] Similar acid leaching and neutralization were also carried out to obtain another neutralized residue B having the components shown in Table 32.
[0136] [Table 32]
[0137] 1.5 g of the neutralized residue B was contacted with water as a liquid, and lithium leaching was performed at 90°C. Here, the pulp concentration was 7.5 g / L, and the leaching time was 300 minutes. The mass and distribution ratio (mass ratio when the components in neutralized residue B are 100) of lithium, aluminum, and calcium contained in the lithium leaching residue (solid) and the lithium-containing solution (liquid) obtained after solid-liquid separation, as well as the mass ratio of the components in neutralized residue B and lithium leaching residue when the components in the battery powder are 100 are shown in Tables 33 and 34, respectively. The pH of the lithium-containing solution was about 5.5 at room temperature.
[0138] [Table 33]
[0139] [Table 34]
[0140] Similar acid leaching and neutralization were also carried out to obtain another neutralized residue C having the components shown in Table 35.
[0141] [Table 35]
[0142] 1.5g of the above neutralization residue C was contacted with the liquid, and lithium leaching was performed under the same conditions. Here, the conditions were changed with respect to the pulp concentration of 7.5g / L or 2.5g / L, and the presence or absence of addition of calcium sulfate. In the test in which calcium sulfate was added, the amount of calcium sulfate added was set to the same mole number as the aluminum in the neutralization residue. The mass and distribution ratio (mass ratio when the components in the neutralization residue C are set to 100) of lithium, aluminum, and calcium contained in the lithium leaching residue (solid) and the lithium-containing solution (liquid) obtained after solid-liquid separation are shown in Tables 36 to 38, respectively. The pH of the lithium-containing solution was about 6 at room temperature.
[0143] [Table 36]
[0144] [Table 37]
[0145] [Table 38]
[0146] From Tables 36 to 38, it can be seen that in the test for neutralization residue C, the leaching of aluminum during lithium leaching could be sufficiently suppressed. It can also be seen that the leaching rate of lithium is increased by lowering the pulp concentration and adding calcium sulfate.
[0147] Similar acid leaching and neutralization were also carried out to obtain another neutralized residue D having the components shown in Table 39.
[0148] [Table 39]
[0149] 1.5 g of the neutralized residue D was contacted with a liquid, and lithium leaching (first lithium leaching) was performed under the same conditions. The lithium leaching residue was then subjected to lithium leaching (second lithium leaching) again using a liquid to which sulfuric acid was added. In the second lithium leaching, the pH when sulfuric acid was added was 3.4 at room temperature, and the amount of sulfuric acid added was 0.5 times the molar amount of lithium in the acid leaching residue. The mass and distribution ratio (mass ratio when the components in the neutralized residue D are 100) of lithium, aluminum, and calcium contained in the lithium leaching residue (solid) and the lithium-containing solution (liquid) obtained after solid-liquid separation in each of the first and second lithium leaching are shown in Tables 40 and 41, respectively. The pH of the lithium-containing solution was about 6 in the first leaching and about 3.5 in the second leaching at room temperature.
[0150] [Table 40]
[0151] [Table 41]
[0152] As shown in Tables 40 and 41, by performing two lithium leaching steps, most of the lithium in the neutralized residue could be leached out.
[0153] From the above, it was suggested that if the lithium-containing solution obtained from the Li-Al-containing material is used in wet processing, it may be possible to suppress lithium loss and effectively utilize the lithium in the Li-Al-containing material.
Claims
1. A method for recovering metals from lithium-ion battery waste by performing wet treatment on battery powder, comprising: a lithium leaching step of contacting a solid Li-Al-containing material containing lithium and aluminum generated by the wet treatment with a liquid, leaching lithium in the Li-Al-containing material into the liquid at a temperature of 70° C. or higher, and performing solid-liquid separation to obtain a lithium-containing solution having a pH of 3 to 10; The method for recovering metals, wherein the lithium-containing solution obtained in the lithium leaching step is used in the wet treatment.
2. The metal recovery method according to claim 1 , wherein the wet treatment includes an acid leaching step in which metals in the battery powder are leached with an acidic leaching solution.
3. The method of claim 2, wherein the lithium-containing solution is used in the acid leaching step.
4. The wet treatment includes a neutralization step of neutralizing the metal-containing solution obtained in the acid leaching step, The method for recovering metals according to claim 2 or 3, wherein the lithium-containing solution is used in the neutralization step.
5. the wet treatment includes a pre-leaching step of leaching lithium in the battery powder before the acid leaching step; The method for recovering metals according to claim 2 or 3, wherein the lithium-containing solution is used in the pre-leaching step.
6. The metal recovery method according to any one of claims 1 to 3, wherein the Li-Al-containing material in the lithium leaching step is an acid leaching residue generated in an acid leaching step in which metals in battery powder of lithium ion battery waste are leached into an acid leaching solution, and / or a neutralization residue generated in a neutralization step in which the metal-containing solution obtained in the acid leaching step is neutralized.
7. The Li-Al containing material is LiCa(AlF 6 7. The metal recovery method according to claim 6, comprising:
8. The metal recovery method according to claim 6, wherein the Li-Al-containing material includes a Li-Al composite hydroxide.
9. 2. The metal recovery method according to claim 1, wherein the Li-Al containing material contains calcium.
10. 2. The metal recovery method according to claim 1, wherein the lithium leaching step is carried out after adding calcium to the Li-Al-containing material.
11. 2. The method for recovering metals according to claim 1, wherein calcium is added to the liquid in the lithium leaching step.
12. The metal recovery method according to any one of claims 9 to 11, wherein the number of moles of calcium in the lithium leaching step is adjusted to be 0.5 to 3.0 times the number of moles of aluminum.
13. The metal recovery method according to any one of claims 1 to 3, wherein water is used as the liquid in the lithium leaching step.
14. The metal recovery method according to any one of claims 1 to 3, wherein the temperature when lithium in the Li-Al-containing material is leached into the liquid in the lithium leaching step is 80°C or higher.
15. The metal recovery method according to any one of claims 1 to 3, wherein the lithium concentration of the lithium-containing solution in the lithium leaching step is 150 mg / L or less.
16. The metal recovery method according to any one of claims 1 to 3, wherein the lithium leaching time in the lithium leaching step is 20 minutes or more.
Citation Information
Patent Citations
How to process lithium-ion battery scrap
JP6801090B2
Method for recovering metals from lithium-ion battery waste
JP7100211B1
Method for recovering metals from lithium-ion battery waste
JP7100217B1